Anthropological Foundation in Karl Rahner’s Concept of Theology. - Jiers, Marcin (Filozofia Chrześcijańska, 2010)
The anthropological turn is one of the main issues in the work of Karl Rahner. The issue tries to find an answer to the question who is man, in the context of the possibility of identifying him as a transcendent being, as a spiritual-personal being connected necessarily to the divine world, that experiences i. a. freedom and responsibility, the components of a set of categories of the human being.